England's Fortress : New Perspectives on Thomas, 3rd Lord Fairfax - Hopper, Andrew; Major, Philip (Ashgate Publishing Ltd, 2014)
Overshadowed in the popular imagination by the figure of Oliver Cromwell, historians are increasingly coming to recognize the importance of Thomas Fairfax, 3rd Lord Fairfax of Cameron, in shaping the events of mid-seventeenth-century Britain. As a military and political figure he played a central role in defeating Charles I and supporting the restoration of Charles II in 1660. This book shines new light on this significant figure through a selection of essays addressing a wide range of topics, from Fairfax's role as soldier and statesman, to his life as husband and scholar.